Structural and Mechanical Comparison of Human Ear, Alar, and Septal Cartilage - Bos, Ernst Jan (Plast Reconstr Surg Glob Open, 2018)
BACKGROUND: In the human ear and nose, cartilage plays a key role in establishing its form and function. Interestingly, there is a noticeable paucity on biochemical, structural, and mechanical studies focused on facial cartilage. Such studies are needed to provide elementary knowledge that is fundamental to tissue engineering of cartilage. Therefore, in this study, a comparison is made of the biochemical, structural, and mechanical differences between ear, ala nasi, and septum on the extracellular matrix (ECM) level. METHODS: Cartilage samples were harvested from 10 cadaveric donors. Each sample was indented 10 times with a nanoindenter to determine the effective Young’s modulus. Structural information of the cartilage was obtained by multiple-photon laser scanning microscopy capable of revealing matrix components at subcellular resolution. Biochemistry was performed to measure glycosaminoglycan (GAG), DNA, elastin, and collagen content. RESULTS: Significant differences were seen in stiffness between ear and septal cartilage (P = 0.011) and between ala nasi and septal cartilage (P = 0.005). Elastin content was significantly higher in ear cartilage. Per cartilage subtype, effective Young’s modulus was not significantly correlated with cell density, GAG, or collagen content. However, in septal cartilage, low elastin content was associated with higher stiffness. Laser microscopy showed a distinct difference between ear cartilage and cartilage of nasal origin. CONCLUSION: Proposed methods to investigate cartilage on the ECM level provided good results. Significant differences were seen not only between ear and nasal cartilage but also between the ala nasi and septal cartilage. Albeit its structural similarity to septal cartilage, the ala nasi has a matrix stiffness comparable to ear cartilage.